Phase‐Transition‐Triggered Optical Switching for Multistage Information Encryption/Decryption. Issue 2 (3rd November 2022) - Xu, Mengda; Qiu, Xiaxin; Liang, Shumin; Huang, Wei; Zhang, Lidong
Abstract: It remains challenging to enable the optical switching for safety‐improved information encryption/decryption on a gel platform. Herein, a water swelling‐induced optical‐switching strategy is reported that can achieve multistage information encryption/decryption on an organohydrogel surface. Cationic moieties of methacrylamido propyl trimethyl ammonium chloride (MPTAC) and hydrophobic fluorophores of (2‐(4‐vinylphenyl) ethene‐1, 1, 2‐triyl) tribenzene (TPE) are copolymerized into hydrophilic polyacrylamide network. The cationic moieties are capable of increasing the water swelling ability of the network, and the fluorophores endow the network with weak blue fluorescence. Upon low swelling with water (swelling ratio in weight < 50), hydrophobic fluorophores of TPE aggregate to enhance the fluorescence under ultraviolet light. This process is accompanied with the phase transition of organohydrogel into a non‐transparent state. After being saturated with water, the fluorescence disappears and the organohydrogel returns to the transparent state. Such water swelling‐induced optical switching can be used for multistage information encryption/decryption with improved safety. Various information patterns are created on the surface of organohydrogel by laser cutting to demonstrate the complex information encryption/decryption processes. This strategy not only provides a meaningful inspiration for information encryption/decryption but also enables an optical‐switching platform for potential anti‐counterfeiting and displaying. Abstract : An optical‐switching organohydrogel is reported by introducing cationic elements and hydrophobic fluorophores into polyacrylamide network, which enables multistage information encryption/decryption, induced by water swelling‐triggered phase transition. This strategy demonstrates apparent improvement of security for information storage.